Pro SQL Azure - Klein, Scott; Roggero, Herve (Apress : Imprint: Apress, 2010)
SQL Azure represents Microsoft's cloud-based delivery of its enterprise-caliber, SQL Server database management system (formerly under the code name "Oslo"). Pro SQL Azure introduces you to this new platform, showing you how to program and administer it in a variety of cloud computing scenarios. You'll learn to program SQL Azure from Silverlight, ASP.NET, WinForms, and from SQL Reporting Services. You'll also understand how to manage the platform by planning for scalability, troubleshooting performance issues, and implementing strong security. Shows how to use SQL Azure from Silverlight, ASP.NET, and more Covers management, scalability, and troubleshooting Addresses the all-important issue of securing your data.